Strategy for Professional Activity Improvement of Teachers of Higher Education Institutions - Sherzod Raxmonovich Urakov (International Journal on Integrated Education, 2023)
In this article, a strategy for improving the activities of professors and teachers of higher education institutions has been developed, in which the directions for the development of professional and pedagogical activities, the valuable, academic, reflexive and student satisfaction criteria for evaluating the professional activity of teachers and related indicators are determined. Additionally, the factors affecting the development of the motivation of professors and teachers for pedagogical activities are revealed.